El efecto del impuesto a la salida de divisas en el sector automotriz, en la ciudad de Machala - Valarezo Ordoñez, Zoila Del Rocio (2017)
The national government in 1998, had to make the necessary adjustments in the country's economy that allowed to control the increase of the interest rate in the credits and, consequently, the restriction of the same. In 1999 the crisis hit bottom, since the president of that then arbitrarily decreed the bank holiday and the freezing of deposits in private banks causing chaos in Ecuador's financial system. In addition, factors such as the liberalization of a deteriorating banking system, the influence of power groups on political decisions, the greater credit demand of multilateral agencies, among others, deepened the critical situation of the country. In 2000, January, dollarization was officially adopted so that the economic crisis could be counteracted in some way. The Central Bank of Ecuador stopped participating in the foreign exchange market and fixed the US dollar exchange rate at 25,000 sucres. Economic stability was momentary, the productive apparatus was reactivated generating GDP growth. On the other hand over the years, inflation reached its highest historical value as a consequence of the accelerated depreciation of the exchange rate, From 2003, a favorable scenario was created for the reactivation of the industrial sector; Which is manifested in a greater participation of the investment in the PIB. Oil exports generated a greater contribution of the external sector in the PIB. The Ecuadorian State through its fiscal policy created the Tax on the Exit of Foreign Exchange in order to discourage the outflow of capital abroad and maintain the investment and reinvestment within the Ecuadorian state with the purpose of attending social progress and stability Economic development of the country.The reason for the present investigation is to know the economic impact of the Exit Tax on the automotive sector in the city of Machala, considering that the automotive sector is one of the most important sectors within the economy of the country, The payment of this tax on imports made by the different entrepreneurs of the city engaged in this business activity Some way in the purchasing power of the people, to make a comparison with the other economic sectors implicit in the payment of ISD.